Modelling angiogenesis in three dimensions - Parsonson, Louis (2015)
The process through which new blood vessels are formed within the body is known as angiogenesis. An essential part of our survival, it has also been implicated more recently in many diseases both in terms of induced growth, and abnormal vascular structure.